Wildfire refugia in forests: Severe fire weather and drought mute the influence of topography and fuel age. (19th July 2019) - Collins, Luke; Bennett, Andrew F.; Leonard, Steve W. J.; Penman, Trent D.
Abstract: Wildfire refugia (unburnt patches within large wildfires) are important for the persistence of fire‐sensitive species across forested landscapes globally. A key challenge is to identify the factors that determine the distribution of fire refugia across space and time. In particular, determining the relative influence of climatic and landscape factors is important in order to understand likely changes in the distribution of wildfire refugia under future climates. Here, we examine the relative effect of weather (i.e. fire weather, drought severity) and landscape features (i.e. topography, fuel age, vegetation type) on the occurrence of fire refugia across 26 large wildfires in south‐eastern Australia. Fire weather and drought severity were the primary drivers of the occurrence of fire refugia, moderating the effect of landscape attributes. Unburnt patches rarely occurred under 'severe' fire weather, irrespective of drought severity, topography, fuels or vegetation community. The influence of drought severity and landscape factors played out most strongly under 'moderate' fire weather. In mesic forests, fire refugia were linked to variables that affect fuel moisture, whereby the occurrence of unburnt patches decreased with increasing drought conditions and were associated with more mesic topographic locations (i.e. gullies, pole‐facing aspects) and vegetation communities (i.e. closed‐forest). In dry forest, the occurrence of refugia was responsive to fuel age, being associated with recently burnt areas (<5 years since fire). Overall, these results show that increased severity of fire weather and increased drought conditions, both predicted under future climate scenarios, are likely to lead to a reduction of wildfire refugia across forests of southern Australia. Protection of topographic areas able to provide long‐term fire refugia will be an important step towards maintaining the ecological integrity of forests under future climate change. Abstract : Fire refugia (i.e. unburnt patches) are important for the persistence of fire‐sensitive species in forests, though the fate of fire refugia under climate change is unknown. Quantification of the relative effects of climate and landscape factors on refugia patterns across Australian temperate forests revealed that fire weather and drought override the effect of topography and fuel age on fire refugia, with less refugia being present under severe fire weather and intense drought. Climate change is likely to lead to the contraction and loss of persistent fire refugia across temperate forests of southern Australia.